Moderate Learning Gains Through PjBL Interactive E Modules: Capaian Belajar Moderat melalui E Modul Interaktif PjBL - Intihana, Muhklisatun; Sumartiningsih, Sri; Prasetya, Agung Tri; Avrilianda, Decky (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Digital transformation in education requires learning media that support active, contextual, and student-centered learning in elementary education. Specific Background Project-Based Learning (PjBL)-based interactive e-modules combine digital content, project activities, and multimedia features to support elementary students’ learning outcomes, engagement, and critical thinking. Knowledge Gap Although previous studies report positive results, the evidence remains limited because the number of reviewed studies is relatively small, research designs vary, and standardized effect size reporting is still lacking. Aims This study aimed to analyze and evaluate PjBL-based interactive e-modules in improving elementary school students’ learning outcomes through a narrative literature review. Results Fifteen articles published between 2020 and 2025 from Scopus, Sinta, and Google Scholar were reviewed. The findings showed a consistent positive trend, with several studies reporting moderate learning gains, approximately 20–30% increases in post-test scores, along with better student engagement and critical thinking skills. The review also identified teacher competency, technological access, and instructional design quality as key moderating factors. Novelty This review synthesizes recent evidence on PjBL-based interactive e-modules by linking learning outcomes with moderating implementation factors and practical development priorities. Implications The findings suggest the need for structured teacher training, standardized interactive module frameworks, and scalable digital infrastructure, while future research should apply meta-analytic approaches and report effect sizes to strengthen the evidence base. Highlights • Fifteen articles from 2020–2025 were synthesized from Scopus, Sinta, and Google Scholar.• Post-test scores showed a consistent 20–30% upward pattern across reviewed studies.• Teacher competency, technological access, and instructional design quality shaped implementation results. Keywords Interactive E Module; Project Based Learning; Learning Outcomes; Elementary School; Critical Thinking